THE EFFECT OF TOTAL LIQUIDITY RATIO, SOLVABILITY RATIO, AND ACTIVITY RATIO THE REMAINING OF BUSINESS PRODUCTS IN KP-RI GKK AIRTIRIS 2010-2019 - Sudarlis Sudarlis; Arman Arman; Sri Mulyani (STIE Bangkinang Publishing, 2022)
This study aims to determine the effect of liquidity ratios, solvency ratios and activity ratios simultaneously or partially on the residual income of the cooperative's employees of the republic of Indonesia, teachers of Kampar sub-district. The data were processed using multiple linear regression analysis techniques. The results of this study indicate that the cash ratio simultaneously has a significant effect on the acquisition of SHU. The closeness of the relationship between the independent variables and the dependent variable is very strong. The size of the relationship between the independent variables and the dependent variable is 70.9%, while the results of the research partially show that the cash ratio variable has a significant effect on the SHU acquisition, while the debt to capital assets and working capital turnover variables do not have a significant effect on the SHU acquisition.